3.5 GHz vivaldi antennas: A feed line analysis for unleashing 5G communication technology - Othman, Mohd Azlishah; Shahirah Ruslan, Nur Aishah; Misran, Mohamad Harris; Meor Said, Maizatul Alice; Abdul Manap, Redzuan; Ja'afar, Abd Shukur; Hassan, Nurmala Irdawaty; Suhaimi, Shadia (Penerbit UTM Press, 2023)
In this study, we discuss the design and testing of a Vivaldi antenna operating at 3.5 GHz, which is well-suited for mobile mid-band 5G connection. CST Microwave Studio software was used to simulate and evaluate the suggested antenna design, which was printed utilising state-of-the-art 3D printing processes and materials (polylactic acid (PLA) and FR-4 circuit board material). The measured results show that the antenna has a reflection frequency of 3.51 GHz and a gain of -23.695 dB. Parametric analysis was carried out to examine the relationship between antenna performance and design parameters, with special focus on the separation between the antenna and the PLA material in the middle of the spherical construction. The Vivaldi antenna is an attractive choice for 5G mid-band applications because of its wideband features, ease of manufacture using typical industrial processes, and simplicity of impedance matching to the feeding line using microstrip line modelling.